Deconstruction and the work of art visual arts and their critique in contemporary French thought - Heikkilä, Martta (Lexington Books, 2021)
"The concept of the "work of art" is paradoxically both widely used and often unexamined. This book re-evaluates the scope of "work," "art," and "the aesthetic" from the viewpoint of deconstructionist philosophy and suggests that Derrida's analyses resolve some central questions in the discourses of contemporary visual arts"--